Analysis of the Effect of Economic, Population, and Energy Growth, as well as the Influence on Sustainable Energy Development in Indonesia - Pasaribu, Faisal Irsan; Cahyadi, Catra Indra; Mujiono, Restu; Suwarno, Suwarno (International Journal of Energy Economics and Policy, 2023)
All economic activities require energy and are natural energy sources that can be utilized as much as possible by the community for prosperity and sustainable development. The potential for renewable/sustainable energy in Indonesia is very large and its utilization has not been maximized. Consumption of sustainable energy according to current data is still very low, this is because it is still dominated by fossil energy. This study aims to analyze the effects of economic growth, population, and subsidized energy, as well as their impact on sustainable energy development. Based on the secondary data used in this study obtained from World Energy, the Indonesian Ministry of Finance, which was obtained in the previous three years (2018-2021). This analysis uses a multiple linear regression model and the results of this research model show that economic growth on population growth does not show a major influence on sustainable energy consumption in Indonesia for three years, fossil fuel energy consumption shows a positive and significant effect on sustainable energy consumption in Indonesia.